2022
DOI: 10.3390/ani12182365
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Selection Signatures in Jianchang Black Goats Revealed by Whole-Genome Sequencing Data

Abstract: Understanding the genetic composition of indigenous goats is essential to promote the scientific conservation and sustainable utilization of these breeds. The Jianchang Black (JC) goat, a Chinese native breed, is solid black, exhibits crude feed tolerance, but is characterized by a low growth rate and small body size. Based on the whole-genome sequencing data for 30 JC, 41 Jintang Black (JT), and 40 Yunshang Black (YS) goats, and 21 Bezoar ibexes, here, we investigated the genetic composition of JC goats by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…The results show a high correlation between ROH and F ROH . In previous studies of the Jianchang black goat [45], there was a strong positive correlation between the number of ROHs on each chromosome and the chromosome length. Similar results were also found in studies of the German white cashmere goat [46].…”
Section: Discussionmentioning
confidence: 75%
“…The results show a high correlation between ROH and F ROH . In previous studies of the Jianchang black goat [45], there was a strong positive correlation between the number of ROHs on each chromosome and the chromosome length. Similar results were also found in studies of the German white cashmere goat [46].…”
Section: Discussionmentioning
confidence: 75%
“…Nonetheless, they have partially clustered together because of breeders’ efforts to improve growth and milk performance of Barki by crossing with Damascus [ 6 ]. The PCA results showed that Damascus and Boer goats are genetically connected, indicating gene flows between these breeds, in contrast to the Egyptian Nubian that was genetically distinct and has a separate genetic structure due to the application of specific breeding programs [ 52 ]. Boer goats were shown to be quite scattered in PCA plot despite implementing some sort of breeding programs.…”
Section: Discussionmentioning
confidence: 99%
“…Two candidate gene were detected on CHR6 at 70.74 and 71.14 Mb: (1) the KIT (KIT Proto-Oncogene, Receptor Tyrosine Kinase) gene, which plays an essential role in the regulation of cell survival and proliferation, hematopoiesis, stem cell maintenance, gametogenesis, mast cell development, migration and function, melanogenesis [ 73 ], and a possible pleotropic role in reproductive performance in livestock. The KIT and its ligand (i.e., KITLG ), are two well-known pigmentation genes in livestock [ 52 , 74 ], and selection signals have been detected in many different goat [ 75 ] and sheep populations [ 76 ]. Interestingly, the same gene was identified to differentiate between the Egyptian Nubian and Boer (F ST = 0.89), which may explain their difference in the dominant hair colors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following recent guidelines, SNP pruning was not applied before ROH detection [40]. The detection of ROHs in LSS and other breeds was carried out using PLINK (v1.9) [33] with the '--homozyg group' command.…”
Section: Genetic Diversity and Genome-wide Detection Of Rohsmentioning
confidence: 99%